Mercury contamination chronologies from Connecticut wetlands and Long Island Sound sediments - Varekamp, J. C.; Kreulen, B.; ten Brink, M. R. B.; Mecray, E. L. (Environmental Geology, 2003)
Sediment cores were used to investigate the mercury deposition histories of Connecticut and Long Island Sound. Most cores show background (pre-1800s) concentrations (50-100 ppb Hg) below 30-50 cm depth, strong enrichments up to 500 ppb Hg in the core tops, with lower Hg concentrations in the surface sediments (200-300 ppb Hg). A sediment core from the Housatonic River has peak levels of 1,500 ppb Hg, indicating the presence of a Hg point source in this watershed. The Hg records were translated into Hg contamination chronologies through Pb-210 dating. The onset of Hg contamination occurred in similar to1840-1850 in eastern Connecticut, whereas in the Housatonic River the onset is dated at around 1820. The mercury accumulation profiles show periods of peak contamination at around 1900 and at 1950-1970. Peak Hg* (Hg* = Hg measured minus Hg background) accumulation rates in the salt marshes vary; dependent on the sediment character, between 8 and 44 ng Hg/cm(2) per year, whereas modern Hg* accumulation rates range from 4-17 ng Hg/cm(2) per year; time-averaged Hg* accumulation rates are 15 ng Hg/cm(2) per year. These Hg* accumulation rates in sediments are higher than the observed Hg atmospheric deposition rates (about 1-2 ng Hg/cm(2) per year), indicating that contaminant Hg from the watershed is focused into the coastal zone. The Long Island Sound cores show similar Hg profiles as the marsh cores, but time-averaged Hg* accumulation rates are higher than in the marshes (26 ng Hg/cm(2) a year) because of-the different sediment characteristics. In-situ atmospheric deposition of Hg in the marshes and in Long Island Sound is only a minor component of the total Hg budget. The 1900 peak of Hg contamination is most likely related to climatic factors (the wet period of the early 1900s) and the 1950-1970 peak was caused by strong anthropogenic Hg emissions at that time. Spatial trends in total Hg burdens in cores are largely related to sedimentary parameters (amount of clay) except for the high inventories of the Housatonic River, which are related to Hg releases from hat-making in the town of Danbury. Much of the contaminated sediment transport in the Housatonic River Basin occurs during floods; creating distinct layers of Hg-contaminated sediment in western Long Island Sound. The drop of about 40% in Hg accumulation rates between the 1960s and 1990s seems largely the result of reduced Hg emissions and to a much lesser extent of climatic factors.
643lmTimes Cited:22Cited References Count:45